KOMITMEN KARYAWAN DAN PRESTASI KERJA - Ricky Ekaputra Foeh (Journal of Management Small and Medium Enterprises (SMEs), 2017)
Affective, Continuing and Normative Commitments the apparatus is a very important part of supportingwork performance, though this is still contradictory by some researchers such as Sommers & Birnbaum(1998); Randall & O'Driscoll (1997); Shore & Wayne (1993); Hackett et al., (1994). The results of thisstudy prove that significant together Affective, Continuous and Normative Commitment to WorkAchievement. The implication of this research is to facilitate the participants to follow the study ofmanagement science related to commitment and job performance, as a reference for further research, and asa benefit for the head of the institution as a memberand to build and to foster commitment of the apparatusto the organization.Keywords: Commitment, Job Performance